Computer programming MOOC for young technology creators: Developmental research - Lepp, Marina; Luik, Piret; Palts, Tauno (Thinking skills and creativity, 2026)
•Limited guidance exists on designing effective MOOCs for young learners.•Applying developmental research yields high MOOC completion success.•Human support is crucial for young learners’ engagement and success in MOOCs.•Voluntary programming MOOCs help students explore their interest in the subject.•Programming MOOC provides opportunities for fostering creative and thinking skills. In modern society, programming has become a valuable skill for everyone. However, a shortage of computer science teachers in schools limits students’ opportunities to develop these skills. To address this gap, developing computer programming MOOCs can be a scalable solution, enabling students to transition from technology users to creators. This paper aims to analyze, describe, and evaluate the development process of the computer programming MOOC “From Technology Consumer to Creator” (TCC) for youths, highlighting its potential to mitigate the shortage of computer science education opportunities. Developmental research design is used to research the TCC course development process. Stages of the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) are used to describe the process. 1386 students from more than half of the secondary-level schools in Estonia participated in the course, and more than 40 % of participants finished the course successfully. Results show that both learners and mentors were satisfied with the topics and course materials and found the course to be useful, interesting, and feasible. Human support from mentors and organizers is more valuable to adolescents than machine support, such as automated feedback. Overall, the TCC course is a good example of an introductory programming MOOC for adolescents, where successful students can continue their studies at the university. The results of our study provide valuable insights for developing programming MOOCs with various engagement strategies for increasing course completion rates for young people, which can benefit other MOOC developers and instructors planning computer science courses for youths.